How many molecules are required to measure a cyclic voltammogram? - Cutress, I; Compton, R (2011)
The stochastic limit at which fully-reversible cyclic voltammetry can accurately be measured is investigated. Specifically, Monte Carlo GPU simulation is used to study low concentration cyclic voltammetry at a microdisk electrode over a range of scan rates and concentrations, and the results compared to the statistical limit as predicted by finite difference simulation based on Fick's Laws of Diffusion. Both Butler-Volmer and Marcus-Hush electrode kinetics are considered, simulated via random-walk methods, and shown to give identical results in the fast kinetic limit. © 2011 Elsevier B.V. All rights reserved.